Sn-containing electrocatalysts with a reduced amount of palladium for alkaline direct ethanol fuel cell applications. (October 2020) - Pinheiro, Victor S.; Souza, Felipe M.; Gentil, Tuani C.; Nascimento, Aline N.; Böhnstedt, Paula; Parreira, Luanna S.; Paz, Edson C.; Hammer, Peter; Sairre, Mirela I.; Batista, Bruno L.; Santos, Mauro C.
Abstract: In this work electrocatalysts based on Pd and Sn nanoparticles supported on Vulcan XC-72 carbon black with a reduced amount of Pd were prepared. We evaluated its electrocatalytic activity for ethanol oxidation reaction (EOR) in alkaline direct ethanol fuel cells (ADEFCs). The electrocatalysts were synthesized in different Pd:Sn mass ratios (1:3, 1:1, 3:1 and 1:0) on the carbon containing 20 wt % of metal. The XRD patterns of the electrocatalysts revealed an alloy formation between Pd and Sn, and the electrocatalysts with lowest amount of Pd (Pd1Sn3/Vulcan XC-72) and highest electrochemically active surface area (ECSA) presented best performance in ADEFC experiments with a maximum current density and power density of 152 mA cm-2 and 42 mW cm-2, respectively. Besides the current density three times higher for EOR than that of the pure Pd, the open circuit potential of 939 mV at an operation temperature of 80 °C yielded the higher carbonate production. This behavior can be attributed to the presence of oxophilic Sn species, which improve the ability to remove adsorbed CO. Oxygenated species, vacancies and defects detected in the structure of PdxSny/Vulcan XC-72 catalysts are accounted for their high activity, making them very promising for the application in ADEFC. Highlights: Pd1 Sn3 /Vulcan XC-72 showed the highest power density (42 mW cm −2 at 80 °C). The cell with Pd1 Sn3 /Vulcan XC-72 showed an open circuit potential of 939 mV. KOH concentration effect study a power density of 42 mW cm −2 was obtained. The good performance can be justified by the higher carbonate formation.